The Secret of Think and Grow Rich - Horowitz, Mitch (Ascent Audio, 2020)
The Secret Revealed Napoleon Hill promises that there is a secret encoded in Think and Grow Rich. Hill writes that the secret appears hundreds of times in his book-but is never directly stated. Now, New Thought scholar and historian Mitch Horowitz reveals to you the master's secret, and explores exactly how to apply it in your life. In The Secret of Think and Grow Rich, Mitch also explores Hill's four most powerful steps, including the intriguing and widely misunderstood question of "sex transmutation." In this short book, Mitch supplies the clearest and most actionable chapter ever written on Hill's method of sex transmutation, a tremendously powerful and under-appreciated part of his wealth-building program. After listening to The Secret of Think and Grow Rich, you will experience Hill's work in a whole new way. Your practice will grow more effective and dynamic-and you will experience positive and radical change. This is the book's promise. Discover it today.